Barus High Board Tomb: Building History Awareness and Religious Tourism Potential - Nurdiansyah Nurdiansyah; Himawan Putra; Dwi Prayoga; Adam William; Alif Maulana; Ahmad Taslih; Gilang Syahrulka; Anrio Hasiolan; Fitria Rosa; Shastela Aisya; Assyifaturramah Assyifaturramah (The Kalimantan Social Studies Journal, 2025)
The High Board Grave in Pananggahan Village, North Barus District, Central Tapanuli Regency, is a historical site with the potential to become a religious tourism destination. The uniqueness of this grave lies in the involvement of non-Muslim local residents in its management and promotion, reflecting a high degree of religious tolerance. In addition to its spiritual significance for pilgrims, the site also has a significant economic impact on the surrounding community, particularly in providing tourism facilities. This study employs a qualitative approach, utilizing interviews with local residents and grave caretakers, as well as a literature review. Data analysis is conducted thematically to identify the socio-economic impacts of religious tourism at the High Board Grave. The findings indicate that this grave has great potential as both a historical and religious tourism destination. Tourism-related activities around the site, such as parking services and pilgrimage facilities, contribute to the local economy. However, challenges persist in managing this tourism sector, particularly regarding inadequate infrastructure and land-use permits.